2020
DOI: 10.1007/s12079-020-00570-7
|View full text |Cite
|
Sign up to set email alerts
|

CircRNA cPWWP2A: an emerging player in diabetes mellitus

Abstract: Circular RNAs(CircRNAs), a new class of non‐coding RNAs, possess significant capabilities of gene regulation and are disrupted in various diseases, including diabetes mellitus (DM). However, the underlying mechanism of CircRNAs in DM and diabetic complications remains illusive. A recent study published by Liu et al. (Proc Natl Acad Sci USA 116:7455–7464, 2019) shown that a novel diabetic retinopathy (DR)‐associated CircRNA cPWWP2A, which could act as a competing endogenous RNA interacting with miR‐579 to promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 10 publications
0
13
0
Order By: Relevance
“…cir-Sry is associated with the occurrence and development of malignant tumors, such as cholangiocarcinoma and colon, ovarian, and pulmonary cancer. 33 These circRNA-miRNA-mRNA interaction networks regulate the occurrence and development of different diseases, including atherosclerosis, 34 Parkinson's disease, 28,35 Alzheimer's disease, 36,37 diabetes, [38][39][40] and pulmonary fibrosis. 41,42 In recent years, the regulatory role of circRNA in tumorigenesis and tumor development has gradually become a new research hotspot.…”
Section: Tricrna Biogenesismentioning
confidence: 99%
“…cir-Sry is associated with the occurrence and development of malignant tumors, such as cholangiocarcinoma and colon, ovarian, and pulmonary cancer. 33 These circRNA-miRNA-mRNA interaction networks regulate the occurrence and development of different diseases, including atherosclerosis, 34 Parkinson's disease, 28,35 Alzheimer's disease, 36,37 diabetes, [38][39][40] and pulmonary fibrosis. 41,42 In recent years, the regulatory role of circRNA in tumorigenesis and tumor development has gradually become a new research hotspot.…”
Section: Tricrna Biogenesismentioning
confidence: 99%
“…Existing studies have used high-throughput sequencing to explore the relationship of the lncRNA-circRNA-miRNA-mRNA network in type 2 diabetes [ 115 ]. Studies have shown that [ 116 ] a new type of diabetic retinopathy (DR) related to circRNA cPWWP2A can interact with miR-579 as a competitive endogenous RNA and promote DR-induced retinal vascular dysfunction by upregulating the expression of angiopoietin 1, occludin, and SIRT1 [ 116 ]. Another study has shown that hsa_circRNA_0054633 is highly expressed in GDM and closely related to the glycosylation index [ 117 ].…”
Section: Othersmentioning
confidence: 99%
“…Many ncRNAs affect specific cellular biological responses, and are key regulatory molecules in the course of disease (20). For example, small ncRNAs, such as, microRNAs (miRNAs), may act as proto-oncogenes or tumor suppressor genes in cancers (21,22); circular RNAs (circRNAs) participate in the development of tumors, neurological diseases, and rheumatic diseases (23)(24)(25); small nucleolar RNAs (snoRNA) participate in tumors, metabolic stress, and other diseases through modification (26,27); long-chain ncRNAs (lncRNAs) have been linked to cancer, diabetes, heart failure, hypertension, kidney disease, and other diseases (28)(29)(30)(31)(32). Thus, ncRNAs are a new hot spot in epigenetic research.…”
Section: Introductionmentioning
confidence: 99%